New records for the bryophyte flora of the Brazilian Amazon - Sierra, Adriel M.; Pereira, Marta Regina Silva; Zartman, Charles Eugene (Rodriguesia, 2019)
Results from recent botanical excursions in northern Brazil include 38 new state and country records. In summary, seven (five liverworts and two mosses) taxa are newly confirmed for Brazil, 18 (10 liverworts and eight mosses) new to Amazonas state and 20 (16 liverworts and four mosses) new to Roraima state. © 2019 Instituto de Pesquisas Jardim Botanico do Rio de Janeiro. All rights reserved.